Factors Affecting Mother Of Doing A Triple Elimination At Uptd Of Palla Public Health Center, North Wewewa Sub-District, Southwest Sumba Regency - Anggrawati Wulandari; Retno Palupi Yonni Siwi; Erma Retnaningtyas; Maria Meilina Billy (Institute of Computer Science (IOCS), 2022)
Triple elimination examination plays an important role in overcoming the transmission of HIV (Human Immunodeficiency Virus), syphilis and hepatitis B in pregnant women to their babies. Factors that influence mothers to perform triple elimination checks include attitudes, husband's support and distance to health services. The purpose of the study was to determine the effect of attitude, husband's support and distance to health services on triple elimination examinations for pregnant women At UPTD of Palla Public Health Center, Wewewa Utara District, Southwest Sumba Regency. The research design used correlation analytic approach cross sectional. The research population was 120 pregnant women and the research sample was 30 respondents with the determination using purposive sampling. The data collection technique used an instrument in the form of a questionnaire sheet. The data analysis method used is the Spearman Rank test. The results showed that most of the 17 (56.7%) respondents had a poor category attitude about the triple elimination examination, most of the 18 (60.0%) respondents received support from their husbands in the lower category, and most of the 21 (70.0%) respondents traveled long distances. to health services in the very far category and almost all 23 (76.7%) respondents did not perform a triple elimination examination. The results of the Spearman Rank prove that the factors that influence the triple elimination examination in pregnant women are attitude (p = 0.000), husband's support (p = 0.000) and distance to health services (p = 0.002). The next researcher needs to know other factors that influence the triple elimination examination, including maternal knowledge and socio-cultural knowledge.